Elevated C-Reactive Protein: Low Quality Sleep as an Inflammation Indicator - Katie Viehmann-Wical; Jerry W. Lee; Seth Wiafe; Matheni Sathananthan; Anna Nelson (Adventist University of Africa, 2022)
Background: High inflammation levels and obesity are each linked to worse health outcomes. Low-quality sleep is linked to higher inflammation. Method: This cross-sectional study investigated whether: individuals with low-quality sleep have higher inflammation; regardless of BMI; low-quality sleep interacts with BMI regarding cross-sectional prediction of inflammation; and whether sleep quality questions could identify this association. We utilized linear regression with 500 African American and Caucasian adults from an Adventist Health Study-2 subset, who completed additional biological indicator testing. Results: Higher total sleep disturbance (TSD) was associated with increased C-reactive Protein (CRP), p= 0.008, (95% CI = 0.22 to 1.42). The interaction of TSD and BMI was significant in a curvilinear association, p = 0.018,(95% CI = -0.05 to -0.01). As TSD increased, CRP increased; however, the association existed primarily in obese individuals (BMI >30). Low-quality sleep is associated with increased CRP levels, which is a consistent inflammation indicator. Conclusion: Obesity was not a risk factor for significantly increased CRP until sleep disturbance was indicated as "often" or "almost every day". This study supports asking sleep quality questions in primary care, for early identification of risk.